Research on Android malware detection based on permission and behavior - Xiao-min ZHANG; Jing LUI; Jun-xi ZHUANG; Ying-xu LAI (网络与信息安全学报)
For the Android platform malicious application,a method of mapping behavior to privilege characteristics by combining static privilege feature analysis and dynamic behavior analysis was proposed,and association analysis algorithm was used to dig out the association rules between privilege features.Feature as a naive Bayesian classification algorithm input,a malicious application detection model was established.Finally,the experiment verify the effectiveness and accuracy of the method.